Building multidisciplinary health workforce capacity to support the implementation of integrated, people-centred Models of Care for musculoskeletal health. Issue 3 (June 2016) - Chehade, M.J.; Gill, T.K.; Kopansky-Giles, D.; Schuwirth, L.; Karnon, J.; McLiesh, P.; Alleyne, J.; Woolf, A.D.
Abstract: To address the burden of musculoskeletal (MSK) conditions, a competent health workforce is required to support the implementation of MSK models of care. Funding is required to create employment positions with resources for service delivery and training a fit-for-purpose workforce. Training should be aligned to define "entrustable professional activities", and include collaborative skills appropriate to integrated and people-centred care and supported by shared education resources. Greater emphasis on educating MSK healthcare workers as effective trainers of peers, students and patients is required. For quality, efficiency and sustainability of service delivery, education and research capabilities must be integrated across disciplines and within the workforce, with funding models developed based on measured performance indicators from all three domains. Greater awareness of the societal and economic burden of MSK conditions is required to ensure that solutions are prioritised and integrated within healthcare policies from local to regional to international levels. These healthcare policies require consumer engagement and alignment to social, economic, educational and infrastructure policies to optimise effectiveness and efficiency of implementation.